Adapting a Theory-Informed Intervention to Help Young Adult Couples Cope With Reproductive and Sexual Concerns After Cancer - Gorman, Jessica R.; Lyons, Karen S.; Reese, Jennifer Barsky; Acquati, Chiara; Smith, Ellie; Drizin, Julia H.; Salsman, John M.; Flexner, Lisa M.; Hayes-Lattin, Brandon; Harvey, S. Marie (Frontiers in Psychology, 2022)
Objective: Most young adults diagnosed with breast or gynecologic cancers experience adverse reproductive or sexual health (RSH) outcomes due to cancer and its treatment. However, evidence-based interventions that specifically address the RSH concerns of young adult and/or LGBTQ+ survivor couples are lacking. Our goal is to develop a feasible and acceptable couple-based intervention to reduce reproductive and sexual distress experience by young adult breast and gynecologic cancer survivor couples with diverse backgrounds. Methods: We systematically adapted an empirically supported, theoretically grounded couple-based intervention to address the RSH concerns of young couples coping with breast or gynecologic cancer through integration of stakeholder perspectives. We interviewed 11 couples (22 individuals) with a history of breast or gynecologic cancer to review and pretest intervention materials. Three of these couples were invited to review and comment on intervention modifications. Content experts in RSH and dyadic coping, clinicians, and community advisors (one heterosexual couple and one LGBTQ+ couple, both with cancer history) participated throughout the adaptation process. Results: Findings confirmed the need for an online, couple-based intervention to support young couples experiencing RSH concerns after breast or gynecologic cancer. Qualitative themes suggested intervention preferences for: 1) A highly flexible intervention that can be tailored to couples’ specific RSH concerns; 2) Active steps to help members of a dyad “get on the same page” in their relationship and family building plans; 3) A specific focus on raising partners’ awareness about how cancer can affect body image and physical intimacy; and 4) Accessible, evidence-based information about RSH for both partners. These results, along with feedback from stakeholders, informed adaptation and finalization of the intervention content and format. The resulting virtual intervention, Opening the Conversation, includes 5 weekly sessions offering training to couples in communication and dyadic coping skills for addressing RSH concerns. Conclusions: The systematic adaptation process yielded a theory-informed intervention for young adult couples facing breast and gynecological cancers, which will be evaluated in a randomized controlled trial. The long-term goal is to implement and disseminate Opening the Conversation broadly to reach young adult couples with diverse backgrounds who are experiencing RSH concerns in cancer survivorship.